Wavelength Independent Photo‐Chemo Tri‐Modal Combinatorial Renal Cell Carcinoma Therapy with Biocompatible Gold‐Titania Nanostars. Issue 1 (6th December 2021) - Kang, Seounghun; Yim, Gyeonghye; Min, Dal‐Hee; Jang, Hongje
Abstract: Chemotherapy is the most commonly used strategy for the treatment of cancer; however, a complete cure is still considered intractable. Although extensive research is being performed to achieve desired therapeutic effects without any side effects, the discovery of an ideal anticancer drug is still not in sight. As a suboptimal solution, sustained‐release using nanoparticles is attempted to enable safe and efficient utilization and delivery of drugs. Moreover, the use of phototherapy to cure drug‐resistant tumors or synergistically amplify the efficacy of anticancer drugs is also being examined. In this study, gold‐titania nanostars (GTN) are synthesized via an extremely facile, safe, and clean route for cancer therapeutic applications. The use of an alcoholic solvent and two metal cations to form GTNs is the only requirement for the preparation of the nanocarriers. GTN shows sufficient colloidal stability, dispersity and biocompatibility for adoption as nanocarriers and photosensitizers. GTN demonstrates a successful sustained release of the hydrophobic drug, sorafenib, and the tri‐modal combinatorial treatment for renal cancer demonstrates potent tumor suppression in vitro and in vivo. Abstract : Nanocarriers with a plasmonic Au nanostar core and a semiconducting TiO2 thin shell are successfully synthesized by a facile, robust, and environmentally friendly one‐pot strategy. Gold‐titania nanostars exhibit excellent biocompatibility and sustained release of the drug sorafenib without toxic responses. Accompanied with photo‐therapeutic strategies, tri‐modal treatment greatly reduces the tumor growth in vitro and in vivo.